PLANT MOISTURE AVAILABILITY ASSESSMENT - N. Muromtsev (Бюллетень Почвенного института им. В.В. Докучаева, 2011)
The regularities of moisture behavior in the system of surface air - vegetation cover - soil with the use of moisture potential are established. It is shown that the moisture potential in soil, leaves of plants, changes in the moisture potential in the soil-plant system, and relative transpiration is related to functional dependencies. It is well established that each group plants (hygrophytes, mesophytesand xerophytes) is characterized a certain narrow range of soil moisture potential, in which the relative transpiration values do not fall below the optimal level (1.0-0.9). This interval is virtually independent of soil properties and meteorological conditions и can be used as the optimal criterion for plant moisture supply.